A rare case of rynopharyngeal melanoma - Francesco Grecchi; Stefano Podrecca; Ilaria Zollino; Valentina Candotto; Francesco Gallo; Giuseppe Rubino; Raffaella Bianco; Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Primary mucosal melanomas (MM) of the head and neck region constitute 0.5-2% of all malignant melanomas. The rynopharynx is a region that is less often involved by malignant melanomas. Because most of mucosal melanotic lesions are painless in their early stages, the diagnosis is unfortunately often delayed until symptoms resulting from ulceration, growth, and/or bleeding are noted. Here, we document the rare case of a malignant rynopharynx melanoma of a 43 year old woman. Its treatment and the pertinent literature are discussed. No complication was recorded in the post-operative period and no further surgery was performed. The follow up showed no recurrence in the same position and with the same characteristics, even after six years. Mucosal melanomas are aggressive tumours and the prognosis in these patients is poor. Clinicians must use treatment strategies that provide functional benefit, so as to maintain quality of life without excessive toxicity.